Bioinformatics analysis reveals the potential role of matrix metalloproteinases in immunity and urolithiasis - Hong, Sen-Yuan; Jiang, Hong-Cheng; Xu, Wen-Chao; Zeng, He-Song; Wang, Shao-Gang; Qin, Bao-Long (Frontiers in Immunology, 2023)
Background The pathogenesis of urolithiasis remains unclear, making the development of medications for treatment and prevention stagnant. Randall’s plaques (RPs) begin as interstitial calcium phosphate crystal deposits, grow outward and breach the renal papillary surface, acting as attachment for CaOx stones. Since matrix metalloproteinases (MMPs) can degrade all components of extracellular matrix (ECM), they might participate in the breach of RPs. Besides, MMPs can modulate the immune response and inflammation, which were confirmed to be involved in urolithiasis. We aimed to investigate the role of MMPs in the development of RPs and stone formation. Methods The public dataset GSE73680 was mined to identify differentially expressed MMPs (DEMMPs) between normal tissues and RPs. WGCNA and three machine learning algorithms were performed to screen the hub DEMMPs. In vitro experiments were conducted for validation. Afterwards, RPs samples were classified into clusters based on the hub DEMMPs expression. Differentially expressed genes (DEGs) between clusters were identified and functional enrichment analysis and GSEA were applied to explore the biological role of DEGs. Moreover, the immune infiltration levels between clusters were evaluated by CIBERSORT and ssGSEA. Results Five DEMMPs, including MMP1, MMP3, MMP9, MMP10, and MMP12, were identified between normal tissues and RPs, and all of them were elevated in RPs. Based on WGCNA and three machine learning algorithms, all of five DEMMPs were regarded as hub DEMMPs. In vitro validation found the expression of hub DEMMPs also increased in renal tubular epithelial cells under lithogenic environment. RPs samples were divided into two clusters and cluster A exhibited higher expression of hub DEMMPs compared to cluster B. Functional enrichment analysis and GSEA found DEGs were enriched in immune-related functions and pathways. Moreover, increased infiltration of M1 macrophages and enhanced levels of inflammation were observed in cluster A by immune infiltration analysis. Conclusion We assumed that MMPs might participate in RPs and stone formation through ECM degradation and macrophages-mediated immune response and inflammation. Our findings offer a novel perspective on the role of MMPs in immunity and urolithiasis for the first time, and provide potential biomarkers to develop targets for treatment and prevention.